La parola del colpevole. A German Life: il fuori campo della Storia, il controcampo delle immagini (Altre Modernità, 2022)
The essay examines A German Life, the interview-documentary of the over a hundred-year-old secretary of Goebbels, Brunhilde Pomsel. Rather than being interested in entering the behind the scenes of the Nazi regime, the film focuses on the marginality of this figure, nonetheless exemplary of the responsibility of German people in the ninetieth century tragedy. Her long account resembles thus a confession, challenged by other documents — the archival materials, mainly Nazi propaganda films, but also educational films made by the Allies — that work as a sort of reverse shot of the witness’ story. The images seem to imply the off-screen of a long-denied truth, but the propaganda quality of such materials reinforces the ambiguity of the testimony, thus revealing its opacity. The difficult access to trauma, its fundamental elusiveness is articulated in-between the visual and the aural, in-between words and images. At the same time, the film makes evident the act of revealing and that of hiding in both the archival materials and in the testimony. The fragmentary nature of the film mirrors that of memory, of its incomplete truth, while the contrast between the visual and the aural, sound and images, is strengthened by the film’s formal choices: the documentary does not resort to the voice over and mostly uses close-ups or extreme close-ups, without leaving escape to the viewer. A German Life, therefore, situates itself in the in-between of the objectivity of a document and the manifest incompleteness of vision, thus reclaiming its testimonial position.
Keywords: witness; guilt; responsibility; document; suspended image